Production and characterization of Bioglass®-titania reinforced hydroxylapatite composite - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
Hydroxylapatite, titania and Bioglass 45S5 are the components generally used for the production of bioactive biomaterials for years. In literature, although the binary composites with the permutation of three components exist, a ternary composite has not yet been tried. Primarily, Bioglass 45S5 was cast, its thermal analysis (Differential thermal analysis (DTA), dilatometric analysis), phase analysis (X-Ray Diffraction (XRD) ), microstructural characterization (Scanning Electron Microscopy (SEM) ) were performed. Then Bioglass 45S5 powder was ground to fine powder to make its particle size closer to the hydroxylapatite and the titania powders. The particle size of the powders were determined using the laser particle sizer. The DTAs of the 3 components, separately and mixed, were performed. They were then mixed, and ball-milled during 24 hours for a better homogenization. Following drying for 24 hours, pellets of 1 inch diameter were obtained using unaxial manuel press and sintered at 1000, 1100, 1200 °C. Mechanical testing (compression and microhardness), porosity measurement (The Archimedes Method), phase determination (XRD) and microstructural characterization (SEM) of the composites were then performed. As a conclusion, when sintering temperature was increased, the porosity in the structure was decreased. Between 1100 °C and 1200 °C, a phase transformation occurred. The results of microhardness ( 24.6, 38.99, 316.2 HV (500gf for 15 sec) for the composites sintered at 1000, 1100, 1200 °C, respectively) and subsequent compression tests (93.023±10.5, 298.14±78.074, 371.9684±38.36 MPa, respectively) approved the possible phase transformation between 1100 °C and 1200 °C along with the XRD results. © (2012) Trans Tech Publications.
Keywords: 45S5 bioglass®; Biocomposite; Hydroxylapatite; Titania